Intracranial-Derived Atherosclerosis Assessment: An In Vitro Comparison between Virtual Histology by Intravascular Ultrasonography, 7T MRI, and Histopathologic Findings - Majidi, S.; Sein, J.; Watanabe, M.; Hassan, A.E.; Van de Moortele, P.-F.; Suri, M.F.K.; Clark, H.B.; Qureshi, A.I. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Atherosclerotic plaque composition and structure contribute to the risk of plaque rupture and embolization. Virtual histology by intravascular ultrasonography and high-resolution MR imaging are new imaging modalities that have been used to characterize plaque morphology and composition in peripheral arteries. MATERIALS AND METHODS: The objectives of this study were 1) to determine the correlation between virtual histology–intravascular ultrasonography and histopathologic analysis (reference standard) and 2) to explore the comparative results of 7T MR imaging (versus histopathologic analysis), both to be performed in vitro by use of intracranial arterial segments with atherosclerotic plaques. Thirty sets of postmortem samples of intracranial circulation were prepared for the study. These samples included the middle cerebral artery (n = 20), basilar artery (n = 8), and anterior cerebral artery (n = 2). Virtual histology–intravascular ultrasonography and 7T MR imaging were performed in 34 and 10 points of interest, respectively. The formalin-fixed arteries underwent tissue processing and hematoxylin-eosin staining. The plaques were independently categorized according to revised Stary classification after review of plaque morphology and characteristics obtained from 3 modalities. The proportion of fibrous, fibrofatty, attenuated calcium, and necrotic components in the plaques were determined in histology slides and compared with virtual histology–intravascular ultrasonography and MR imaging. RESULTS: Of 34 points of interest in the vessels, 32 had atherosclerotic plaques under direct visualization. Plaques were visualized in gray-scale intravascular ultrasonography as increased wall thickness, outer wall irregularity, and protrusion. The positive predictive value of virtual histology–intravascular ultrasonography for identifying fibroatheroma was 80%. Overall, virtual histology–intravascular ultrasonography accurately diagnosed the type of the plaque in 25 of 34 samples, and κ agreement was 0.58 (moderate agreement). The sensitivity and specificity of virtual histology–intravascular ultrasonography readings for fibroatheroma were 78.9% and 73.3%, respectively. The overall sensitivity and specificity for virtual histology–intravascular ultrasonography were 73.5% and 96.6%, respectively. Plaques were identified in 7T MR imaging as increased wall thickness, luminal stenosis, or outer wall protrusion. The positive predictive value of 7T MR imaging for detecting fibrous and attenuated calcium deposits was 88% and 93%, respectively. CONCLUSIONS: This in vitro study demonstrated that virtual histology–intravascular ultrasonography and high-resolution MR imaging are reliable imaging tools to detect atherosclerotic plaques within the intracranial arterial wall, though both imaging modalities have some limitations in accurate characterization of the plaque components. Further clinical studies are needed to determine the clinical utility of plaque morphology and composition assessment by noninvasive tests. IVUSintravascular ultrasonographySPACEsampling perfection with application-optimized contrasts by use of different flip angle evolutionsVHvirtual histology